Respuesta :
Answer:
(a) [tex]E(r) = \frac{a}{4\pi \epsilon_0}(2-\frac{r}{R})[/tex]
(b) [tex]E(r) = \frac{1}{4\pi\epsilon_0}\frac{aR}{r}[/tex]
(c) The results from part (a) and (b) agree at r = R.
Explanation:
(a) r < R:
The electric field can be found by Gauss' Law, since the insulating cylinder is very long.
We will choose an cylinder shaped-Gaussian surface which is imaginary, only to use the Gauss' Law. The radius of the imaginary cylinder will be 'r'. Then by Gauss' Law, the electric flux flowing through this imaginary surface is equal to the enclosed charge trapped inside the imaginary cylinder.
[tex]\int {\vec{E}} \, d\vec{a} = \frac{Q_{enc}}{\epsilon_0}[/tex]
Let us denote the length of the imaginary cylinder as 'h'.
Since we chose a symmetric geometry (cylinder) as Gaussian surface, we do not need to take the integral in the left-hand side of the Gauss' Law. It is simply
[tex]\int \, da = 2\pi rh[/tex]
The enclosed charge can be calculated by integrating the volume charge density over the imaginary cylinder.
[tex]Q_{enc} = \int\limits^r_0 {\rho(r)h} \, dr = ah\int\limits^r_0 {(1 - \frac{r}{R})} \, dr = ah(r - \frac{r^2}{2R})\left \{ {{r=r} \atop {r=0}} \right. = ah(\frac{2rR - r^2}{2R})[/tex]
The Gauss' Law can now be solved.
[tex]E(r)2\pi rh = ah\frac{2rR - r^2}{2\epsilon_0 R}\\E(r) = \frac{a}{4\pi \epsilon_0}\frac{2R - r}{R}\\E(r) = \frac{a}{4\pi \epsilon_0}(2-\frac{r}{R})[/tex]
It can be seen that 'h' is canceled out, because the length of the imaginary surface has no effect on the Electric field at r.
(b) r > R:
A similar approach will be followed, although this time the enclosed charge will be the cylinder itself.
[tex]Q_{enc} = \int\limits^R_0 {\rho(r)h} \, dr = ah\int\limits^R_0 {(1-\frac{r}{R})} \, dr = ah(r - \frac{r^2}{2R})\left \{ {{r=R} \atop {r=0}} \right. = ah(R-\frac{R^2}{2R}) = ah\frac{R}{2}[/tex]
Now, Gauss' Law can be solved.
[tex]E(r)2\pi rh = \frac{ahR}{2\epsilon_0}\\E(r) = \frac{1}{4\pi\epsilon_0}\frac{aR}{r}[/tex]
(c) r = R:
[tex]E(r) = \frac{a}{4\pi \epsilon_0}(2-\frac{r}{R})\\E(r) = \frac{1}{4\pi\epsilon_0}\frac{aR}{r}\\\\E(r) = \frac{a}{4\pi\epsilon_0}[/tex]
For both parts E(R) is equal to each other.